Characterization of Capacitor-based Reconfigurable Frequency Selective Surfaces - Achmad Munir; Arif Jauhari (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
In this paper, the characterization of reconfigurablefrequency selective surfaces (FSS) based on capacitoris numerically investigated. The capacitor is applied to controlthe characteristic response, i.e. reflectivity, of FSS. A simplerectangular patch with the total length of 130mm and thewidth of 0.6mm which has 2 resonant frequencies at 2.4GHzand 4GHz is used as basis of reconfigurable FSS construction.The investigation is conducted by varying the patch shape andthe capacitance value. The relationship of patch shape and thepresence of capacitor to the characteristic response of FSS isanalyzed, first, by proposing the initial construction which isdivided into 2 identical parts. Secondly, the variation of up andbottom width of patch without modifying the center side, so theconstruction becomes a bow-tie shape, is carried out. In the last, acapacitor is applied in the middle of patch to obtain the variationof characteristic response. From the characterization result, itshows that the higher capacitance value affects to the reflectivityof lower frequency response.